Pakpak Architecture, A Study of Local/Traditional Architecture for Architect Licensing in North Sumatra - Peranita Sagala (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
Traditional architecture in North Sumatra is very diverse. There are eight types of traditional houses in North Sumatra, and each tribe also has a diversity of traditional architecture. This research summarises the diversity of local architecture, especially traditional Pakpak architecture in North Sumatra, to be used as a guide in the application of architect licensing in North Sumatra.The method used is literature study and sorting out aspects of architecture that are important to understand. These aspects are historical background, settlement patterns, building types, ornaments and examples of their application. From this research, it was found that there is a lack of scientific literature documenting traditional Pakpak architecture in North Sumatra. It is hoped that this research will encourage further research into traditional architecture which is still very under-researched.